(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
Devdutt Pattanaik, a renowned Indian author and mythologist, has significantly contributed to the interpretation and understanding of Indian mythology through his extensive body of work. His writings blend ancient narratives with contemporary relevance, shedding light on themes such as dharma, karma, and the human condition. Pattanaik’s unique approach intertwines storytelling, symbolism, and cultural analysis, offering a fresh perspective on myths that have shaped Indian culture and traditions. By exploring texts like the Mahabharata, Ramayana, and Puranas, he delves into the complexities of human behavior, ethical dilemmas, and the societal constructs embedded within these stories. Furthermore, Pattanaik emphasizes the universality of myths, bridging cultural gaps and connecting Indian mythology to global narratives. His works also examine the role of mythology in modern contexts, including leadership, management, and personal growth, illustrating their timeless relevance. Through his vivid storytelling and engaging illustrations, Pattanaik not only decodes symbolic imagery but also highlights the importance of multiple perspectives in interpreting myths. This study aims to analyze the recurring themes, symbolism, and cultural insights in Pattanaik’s works, examining their impact on understanding Indian mythology and their contribution to popularizing ancient narratives for contemporary audiences. By doing so, it seeks to understand how his interpretations challenge conventional readings and provide a more inclusive and dynamic approach to mythology.